Territories development tax incentives - N. Z. Zotikov (Вестник университета)
Nowadays, the regions of the Russian Federation are developing extremely unevenly. The fiscal mechanism and its major part – the tax incentives for economic entities activities, operating in regions and municipalities, play a special role in the successful territories’ development provision. The importance and relevance of the territories tax incentives is due to the necessity to solve the set tasks for the regional economy sustainable development, identify and effectively implement the tax potential in the territories, and it is complicated by the fact that, according to Rosstat, ¼ of the country’s population, living in municipalities and rural settlements, according to established practice, experiencing more financial difficulties than the rest of the population. The existing fiscal mechanism does not create incentives for the successful regional development, especially municipalities, which ultimately does not ensure the country’s successful economic development as a whole. It is impossible to change the situation without creating an effective taxation mechanism.